(untitled) (MAUSAM, 1984)
Seasonal rainfall departures for the period 1875-1974 have been subjected by Markov Chain analysis to determine the conditional probabilities of drought/non-drought years. This has been done by selecting one meteorological sub-division, from each of the climatic type, viz., per-humid, humid, sub-humid (dry and moist), semi-arid and arid regions. Expected length of climatic cycles, that is, drought spell followed by a non-drought spell and vice versa, have also been computed and discussed.